Housing Financialization and the State, in and Beyond Southern Europe: A Conceptual and Operational Framework - Tulumello, Simone (2023)
This article sets out a conceptual/operational framework designed to analyse how the state has enabled, promoted and shaped housing financialization. We build on the systematic analysis of literature and legislation in Portugal, Spain, Italy and Greece, thereby providing an overview of housing financialization in Southern Europe. We identify six modes of housing financialization (mortgage debt, mortgage securitization, social rented housing, market rental housing, housing companies, “not-for-housing housing”), characterized by relative autonomy and specific mechanisms, plus a number of cross-cutting dimensions. Our conceptual/operational framework allows to systematically inquiry whether the state has passively adapted to global transformations or shaped these transformations in turn, therefore advancing two main contributions: first, contributing to a more precise conceptualization of the mechanisms of housing financialization; and, second, providing operational instruments to explore state action and policy in housing financialization beyond Southern Europe.